Pengaruh Media Diorama Augmented Reality terhadap Hasil Belajar IPA Siswa Kelas V SDN 28 Parepare - Usman Usman; Zaid Zainal; Ummil Khaer Kadir (Lembaga Yasin AlSys, 2026)
Although the use of innovative learning media in science learning has been widely studied, research that specifically discusses the integration of ecosystem dioramas with augmented reality technology at the elementary school level remains limited. This study aimed to analyze the effect of applying augmented reality-based ecosystem diorama media on the science learning outcomes of elementary school students. This study used a quantitative approach with a quasi-experimental design, specifically an unequal control group, with sampling carried out through a cluster random sampling technique. Data were collected using test instruments in the form of a pretest and a posttest. Data analysis was conducted through descriptive and inferential statistics, including the N-Gain test, normality, homogeneity, and the independent samples t-test. The results showed a significant difference in learning outcomes between the experimental group and the control group, with the experimental group obtaining a higher mean score. The results of the independent samples t-test showed a significance value (Sig. 2-tailed) below 0.05, indicating that the use of augmented reality-based ecosystem diorama media had a significant effect on students’ science learning outcomes. These findings provide a theoretical contribution to the development of interactive learning media and enrich the literature on technology integration in science education at the elementary school level. The conclusion of this study confirms that the integration of ecosystem diorama media with augmented reality is effective in improving student learning outcomes, so it can serve as an alternative technology-based learning medium to create a more meaningful science learning experience.